Surgical hernia - Biomechanical and physiopathological basis of their treatment. - Croci, Fabio; Gastambide, Carmelo; Cordal, Adriana; Pérez Penco, Ernesto; Terra, Eneas (Cirugía del Uruguay, 1984)
Surgical hernia is more than a failure in parietal repairing, it is a complex disease that involves respira• tory, vascular and visceral aspects. lts solution by sur• gery is not simple in ali cases and the failure rate is an average of 8-10%. More than from technical defect, fallures result from faulty means to determine the m,ethods to be employed due to lack of a proper knowledge of the biomechanics and physiopathology of the altered abdominal wall.